Preparation of core-shell flower-like COF and application of core-shell flower-like COF in separation and purification of active ingredients of cistanche
Covalent bonding TPB and DVA to form a core-shell flower-like COF material, the existing adsorbents have small surface area, fixed pore size distribution, and low adsorption selectivity when separating and purifying ACT in Cistanche, and achieved efficient ACT adsorption and separation and purification effects.
Patent Information
- Application Number
- CN202411932344.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-15
AI Technical Summary
When existing adsorbents are isolated and purified in Cistanche, the surface area is small, the pore size distribution and structure are fixed, the adsorption selectivity is not high, and the synthesis process is complicated.
Covalent bonds are used to connect TPB and DVA to form a building block with vinyl side chains. A bottom-up self-assembly strategy is used to prepare a core-shell flower-like COF material as an adsorbent. The method is carried out at room temperature, with simple operation, large specific surface area of the material, adjustable pore distribution and structure, and high adsorption selectivity.
Highly efficient adsorption of ACT was achieved, with the highest adsorption amount being 479.75±6.43 mg/g and the maximum selectivity being 3.47±0.01. It has good applications in the separation of natural products, especially the separation and purification of active ingredients of Cistanche.
Smart Images

Figure HDA0005210659230000011 
Figure HDA0005210659230000012 
Figure HDA0005210659230000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical fields of covalent organic framework material preparation, natural product separation and purification, and adsorbent preparation, and specifically relates to a method for preparing a core-shell flower-shaped COF material and its application in separating and purifying active ingredients in Cistanche deserticola. Background Art
[0002] ACT is a natural product, mainly extracted from phenylethanol glycoside compounds in Cistanche deserticola. It has strong biological and pharmacological activities. Studies have shown that ACT has neuroprotective effects and can effectively repair damaged neurons. In addition, ACT also has anti-atherosclerotic effects. It can also inhibit the growth of tumor cells. Therefore, it has aroused great interest in the medical field, food and health care products. However, the content of ACT in Cistanche deserticola is very low. It is a challenge to obtain high-purity ACT, so it is very important to develop an effective method for separating and purifying ACT. Most of the active ingredients of natural products are not resistant to high temperature, acid and alkali, etc., which limits the separation method of active ingredients.
[0003] The selection of ACT separation and purification process depends on many factors, including purity, recovery rate and selectivity. Among them, adsorbent separation method is considered to be one of the most promising ACT separation and purification technologies because of its advantages of high efficiency, easy regeneration, low energy consumption and simple operation. Adsorbents usually work in two ways: physical adsorption and chemical adsorption. Physical adsorption involves intermolecular forces, such as van der Waals forces and electrostatic forces, and is usually carried out at low temperature and high pressure; chemical adsorption involves the formation of chemical bonds between adsorbed molecules and adsorbents, which requires a certain activation energy, has high adsorption energy and a relatively permanent adsorption process. Common adsorbents include activated carbon, molecular sieves, silica gel, activated alumina, etc. They have large specific surface area, suitable pore structure and surface structure, but the above methods have relatively small specific surface area, relatively fixed pore size distribution and structure, low adsorption selectivity, strong adsorption limitations, and relatively complex synthesis process. Therefore, it is necessary to develop an adsorbent with larger specific surface area, adjustable pore distribution and structure, large adsorption selectivity and simple synthesis process as an adsorption material for ACT. Summary of the invention
[0004] In view of some deficiencies in the prior art, the present invention provides a method for preparing a core-shell flower-shaped COF material and application thereof in the separation and purification of active ingredients of Cistanche deserticola. The present invention is based on the network chemistry principle and forms a COF material by connecting molecular building blocks through covalent bonds. In the core-shell flower-shaped COF material, TPB and DVA form building blocks with vinyl side chains through Schiff base reaction, and a flower-shaped COF with a core-shell structure is formed through a bottom-up self-assembly strategy. The growth process of the flower-shaped COF is affected by the reaction time, resulting in different cavity structures formed at different reaction times, and the solid flower shape is transformed into a core-shell flower-shaped COF adsorbent. The core-shell flower-shaped COF adsorbent can be used as an adsorbent material for separation and purification. The preparation process of the core-shell flower-shaped COF adsorbent is simple, the reaction is controllable, and the conditions are mild. The core-shell flower-shaped COF adsorbent has good application in the separation of natural products, especially the separation and purification of active ingredients of Cistanche deserticola.
[0005] In order to achieve the above technical effects, the present invention adopts the following technical means:
[0006] The present invention first provides a core-shell flower-shaped COF material. The core-shell flower-shaped COF material is formed by Schiff base condensation of TPB and DVA, wherein TPB and DVA are self-assembled by Schiff base condensation to form building blocks with vinyl side chains; the core-shell flower-shaped COF presents a 3D spherical structure.
[0007] The present invention also provides a method for preparing the core-shell flower-shaped COF material, comprising the following steps:
[0008] (1) TPB and DVA are added to a beaker, and then acetonitrile and water are added thereto to obtain a solution A, and the solution A is subjected to ultrasonic treatment at room temperature to obtain a suspension B;
[0009] (2) adding glacial acetic acid to suspension B and ultrasonically treating the suspension at room temperature to obtain suspension C, which is then sealed and allowed to stand at a certain temperature, centrifuged, washed, and dried to obtain the core-shell flower-like COF.
[0010] Preferably, in step (1), the dosage of TPB and DVA is in the following relationship: 0.01-0.1 mmol: 0.01-0.1 mmol;
[0011] The beaker has a capacity of 10 mL;
[0012] The solvent comprises a mixed solution of acetonitrile and water, wherein the volume ratio of acetonitrile to water in the mixed solution is 4.5 mL:0.5 mL;
[0013] The ultrasonic treatment time is 1 to 5 minutes.
[0014] Preferably, in step (2), the volume of glacial acetic acid is 0.1 to 1 mL;
[0015] The ultrasonic treatment time is 1 to 5 minutes;
[0016] The sealed and static condition at a certain temperature is sealed and static for 10 to 72 hours at 25 to 35°C.
[0017] The present invention also provides application of the core-shell flower-shaped COF material in separation and purification of natural products.
[0018] Preferably, the application includes: separation and purification of active ingredients of Cistanche deserticola.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention provides a core-shell flower-like COF material. Different from the prior art, in the core-shell flower-like COF material of the present invention, TPB and DVA are reacted through a Schiff base to form a building block with a vinyl side chain, and a flower-like COF with a core-shell structure is formed through a bottom-up self-assembly strategy. The method can be carried out at room temperature, is simple to operate, and the synthetic material has a larger specific surface area, adjustable pore distribution and structure, and high adsorption selectivity.
[0021] (2) The core-shell flower-shaped COF material of the present invention contains a large number of vinyl side chains and some amino functional groups that can interact with the nucleophilic sites of ACT, thereby enhancing the interaction between the core-shell flower-shaped COF material and ACT. Therefore, the core-shell flower-shaped COF material of the present invention effectively improves the adsorption selectivity of ACT.
[0022] (3) The core-shell flower-like COF material of the present invention has a mesoporous structure on the surface and an internal core-shell cavity structure as an adsorbent to construct a rich transfer path inside, thereby improving the adsorption selectivity of the core-shell flower-like COF material for ACT. The preparation process of the core-shell flower-like COF material is simple, the reaction is controllable, and the conditions are mild. The research results show that the core-shell flower-like COF material of the present invention has a maximum adsorption capacity of 479.75±6.43 mg / g for ACT, and a maximum selectivity for ACT of 3.47±0.01, which has good application in the separation of natural products, especially the separation and purification of the active ingredients of Cistanche deserticola. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a transmission electron microscope image of the material HF-COF-1 of Example 1 (scale is 200 nm).
[0024] Figure 2 This is a transmission electron microscope image of the material HF-COF-2 of Example 2 (scale is 200 nm).
[0025] Figure 3This is a transmission electron microscope image of the material HF-COF-3 of Example 3 (scale is 200 nm).
[0026] Figure 4 This is a transmission electron microscope image of the material HF-COF-0.5 of comparative example 1 (scale is 200 nm).
[0027] Figure 5 These are the PXRD patterns of HF-COF-1, HF-COF-2, HF-COF-3, and HF-COF-0.5.
[0028] Figure 6 This is a scanning electron microscope image of the material HF-COF-1 of Example 1 (scale is 500 nm).
[0029] Figure 7 This is a scanning electron microscope image of the material HF-COF-2 of Example 2 (scale is 500 nm).
[0030] Figure 8 This is a scanning electron microscope image of the material HF-COF-3 of Example 3 (scale is 500 nm).
[0031] Fig. 9 This is a scanning electron microscope image of the material HF-COF-0.5 of comparative example 1 (scale is 500 nm). DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto. Experimental methods without specific conditions in the embodiments are all based on conventional conditions; the reagents and materials used, unless otherwise specified, can be obtained from commercial sources.
[0033] Example 1: Preparation of HF-COF-1
[0034] (1) 14.06 mg of TPB and 11.17 mg of DVA were added to a 10-mL beaker, and then 4.5 mL of acetonitrile and 0.5 mL of water were added thereto to obtain solution A; solution A was ultrasonically treated at room temperature for 1 min to obtain suspension B.
[0035] (2) 0.8 mL of glacial acetic acid was added to the suspension B and ultrasonically treated at room temperature for 1 min to obtain a suspension C, which was then sealed and allowed to stand at room temperature for 24 h before centrifugation, washing, and drying to obtain the HF-COF-1.
[0036] Figure 1 This is the transmission electron microscopy image of HF-COF-1. Figure 6 This is a scanning electron microscope image of HF-COF-1. Figure 1 , Figure 6It can be seen that HF-COF-1 presents a 3D spherical core-shell flower-like morphology; the amino group of TPB reacts with DVA through a Schiff base reaction to form a C=N bond, so that TPB and DVA are successfully composited.
[0037] Figure 5 This is the XRD diagram of the flower-like COF. It can be seen from the figure that the diffraction peaks of the flower-like COF appear correspondingly, which indicates that the flower-like COF is successfully synthesized.
[0038] This example also performs a performance test on the prepared HF-COF-1 adsorbent, and the test steps are as follows:
[0039] (1) The prepared HF-COF-1 was used for ACT / ECH adsorption selectivity test;
[0040] (2) A mixed solution of 0.5 mg / mL ACT and 0.5 mg / mL ECH was prepared in a conical flask and 10 mg of HF-COF-1 material was added. The solution was placed in a shaker (150 rpm) for adsorption for 24 h. After that, samples were taken and the amount of solute in the solution was measured using high performance liquid chromatography.
[0041] The test results show that its ACT adsorption capacity is 320.07 mg / g and the selectivity is 2.89.
[0042] Example 2: Preparation of HF-COF-2
[0043] (1) 14.06 mg of TPB and 11.17 mg of DVA were added to a 10-mL beaker, and then 4.5 mL of acetonitrile and 0.5 mL of water were added thereto to obtain solution A; solution A was ultrasonically treated at room temperature for 1 min to obtain suspension B.
[0044] (2) 0.8 mL of glacial acetic acid was added to the suspension B and ultrasonically treated at room temperature for 1 min to obtain a suspension C, which was then sealed and allowed to stand at room temperature for 48 h before centrifugation, washing, and drying to obtain the HF-COF-2.
[0045] Figure 2 This is the transmission electron microscope image of HF-COF-2. Figure 7 This is a scanning electron microscope image of HF-COF-2. Figure 2 , Figure 7 It can be seen that HF-COF-2 presents a 3D spherical flower-like morphology; the amino group of TPB reacts with DVA through a Schiff base reaction to form a C=N bond, so that TPB and DVA are successfully composited.
[0046] Figure 5 This is the XRD diagram of the flower-like COF. It can be seen from the figure that the diffraction peaks of the flower-like COF appear correspondingly, which indicates that the flower-like COF is successfully synthesized.
[0047] The adsorption selectivity of HF-COF-2 was tested by the method described in Example 1. The test showed that the adsorption amount of ACT was 351.33 mg / g and the selectivity was 2.80.
[0048] Example 3: Preparation of HF-COF-3
[0049] (1) 14.06 mg of TPB and 11.17 mg of DVA were added to a 10-mL beaker, and then 4.5 mL of acetonitrile and 0.5 mL of water were added thereto to obtain solution A; solution A was ultrasonically treated at room temperature for 1 min to obtain suspension B.
[0050] (2) 0.8 mL of glacial acetic acid was added to the suspension B and ultrasonically treated at room temperature for 1 min to obtain a suspension C, which was then sealed and allowed to stand at room temperature for 72 h before centrifugation, washing, and drying to obtain the HF-COF-3.
[0051] Figure 3 This is the transmission electron microscope image of HF-COF-3. Figure 8 This is a scanning electron microscope image of HF-COF-3. Figure 2 , Figure 7 It can be seen that HF-COF-3 presents a 3D spherical flower-like morphology; the amino group of TPB reacts with DVA through a Schiff base reaction to form a C=N bond, so that TPB and DVA are successfully composited.
[0052] Figure 5 This is the XRD diagram of the flower-like COF. It can be seen from the figure that the diffraction peaks of the flower-like COF appear correspondingly, which indicates that the flower-like COF is successfully synthesized.
[0053] The adsorption selectivity of HF-COF-3 was tested by the method described in Example 1. The adsorption amount of ACT was 277.58 mg / g and the selectivity was 2.99.
[0054] Comparative Example 1: Preparation of HF-COF-0.5
[0055] (1) 14.06 mg of TPB and 11.17 mg of DVA were added to a 10-mL beaker, and then 4.5 mL of acetonitrile and 0.5 mL of water were added thereto to obtain solution A; solution A was ultrasonically treated at room temperature for 1 min to obtain suspension B.
[0056] (2) 0.8 mL of glacial acetic acid was added to the suspension B and subjected to ultrasonic treatment at room temperature for 1 min to obtain a suspension C, which was then sealed and allowed to stand at room temperature for 12 h before centrifugation, washing, and drying to obtain the HF-COF-0.5.
[0057] Figure 4This is the transmission electron microscope image of HF-COF-0.5. Fig. 9 This is a scanning electron microscope image of HF-COF-0.5. Figure 2 , Figure 7 It can be seen that HF-COF-0.5 presents a 3D spherical flower-like morphology; the amino group of TPB reacts with DVA through a Schiff base reaction to form a C=N bond, so that TPB and DVA are successfully composited.
[0058] Figure 5 This is the XRD diagram of the flower-like COF. It can be seen from the figure that the diffraction peaks of the flower-like COF appear correspondingly, which indicates that the flower-like COF is successfully synthesized.
[0059] The adsorption selectivity of HF-COF-0.5 was tested by the method described in Example 1. The adsorption amount of ACT was 287.35 mg / g and the selectivity was 3.07.
[0060] In summary, the present invention is based on the network chemistry principle, and forms a COF material by connecting molecular building blocks through covalent bonds; in the core-shell flower-like COF material, TPB and DVA form building blocks with vinyl side chains through Schiff base reaction, and a flower-like COF with a core-shell structure is formed through a bottom-up self-assembly strategy; the growth process of the flower-like COF is affected by the reaction time, resulting in different cavity structures formed at different reaction times, and the solid flower shape is transformed into a core-shell flower-like COF adsorbent; the core-shell flower-like COF adsorbent can be used as an adsorbent material for separation and purification; the preparation process of the core-shell flower-like COF adsorbent is simple, the reaction is controllable, and the conditions are mild, and it has good application in the separation of natural products, especially the separation and purification of active ingredients of Cistanche deserticola.
[0061] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A method for preparing a core-shell flower-shaped COF material, characterized in that: The steps include: (1) TPB and DVA are added to a beaker, and then acetonitrile and water are added thereto to obtain solution A, and solution A is subjected to ultrasonic treatment at room temperature to obtain suspension B; glacial acetic acid is added to suspension B and ultrasonic treatment is performed at room temperature to obtain suspension C, which is then sealed and allowed to stand at a certain temperature, centrifuged, washed, and dried to obtain the core-shell flower-shaped COF.
2. The method for preparing the core-shell flower-shaped COF according to claim 1, characterized in that: In step (1), the dosage of TPB and DVA is in the following relationship: 0.01-0.1 mmol: 0.01-0.1 mmol; The beaker has a capacity of 10 mL; The solvent comprises a mixed solution of acetonitrile and water, wherein the volume ratio of acetonitrile to water in the mixed solution is 4.5 mL:0.5 mL; The ultrasonic treatment time is 1 to 5 minutes; The volume of the glacial acetic acid is 0.1-1 mL; The ultrasonic treatment time is 1 to 5 minutes; The sealed and static condition at a certain temperature is sealed and static for 10 to 72 hours at 25 to 35°C.
3. The core-shell flower-shaped COF prepared according to any one of claims 1 to 3, characterized in that: The core-shell flower-shaped COF is formed by condensation of TPB and DVA through Schiff base, and the TPB and DVA are self-assembled by forming building blocks with vinyl side chains through Schiff base condensation; the core-shell flower-shaped COF presents a 3D spherical structure.
4. Use of the core-shell flower-shaped COF material according to claim 3 in the separation and purification of natural products.
5. The use according to claim 4, characterized in that: The application includes: separation and purification of active ingredients of Cistanche deserticola.